Role of Multistrain Probiotics in Presentation of Severity and Frequency of Upper Respiratory Tract Infection - Akhtiar, Dua; Masood, Shaheen; Nasruddin, Aamir; Anwer, Tayyaba; Memon, Kiran; Faridi, Taimur Naeem (Biological and Clinical Sciences Research Journal, 2025)
Upper respiratory tract infections (URTIs) are a common health issue that significantly impact individuals’ quality of life. Probiotic supplementation has been suggested as a potential intervention to reduce URTIs’ frequency, severity, and duration. Objective: This study aimed to evaluate the role of multistrain probiotics in the presentation of severity and frequency of URTIs. Methods: This cross-sectional study was conducted at Abbasi Shaheed Hospital, Karachi, during July 2024 to December 2024. The study involved a total of 185 patients, aged between 4 and 12 years. Data collection was carried out in two phases: baseline and follow-up. At baseline, participants underwent a thorough medical examination and completed questionnaires assessing their general health and history of respiratory infections. Results: The treatment group experienced a significantly lower frequency of URTIs (1.14 episodes per participant) compared to the other group (2.03 episodes per participant, p < 0.01). Symptom severity, as indicated by the Jackson score, was significantly reduced in the probiotic group (2.3 ± 0.8) compared to the other group (3.4 ± 1.1, p < 0.05). The duration of illness was also shorter in the treatment group (4.5 ± 1.2 days) compared to the other group (6.2 ± 1.5 days, p < 0.01). Immune markers showed a favorable response in the probiotic group, with reduced IL-6 levels and increased IL-10. Conclusions: Multistrain probiotics significantly reduce the frequency, severity, and duration of URTIs. The probiotics also positively impact immune function and quality of life, with minimal side effects. These findings suggest that multistrain probiotics could be a helpful adjunct in preventing and reducing the severity of URTIs, particularly in individuals prone to recurrent infections.